The Syndrome Bit Flipping Algorithm for LDPC Codes - Boutillon, Emmanuel; Winstead, Chris; Ghaffari, Fakhreddine (IEEE communications letters, 2023)
Performance of LDPC decoders at high SNR is dominated by trapping sets that induce an error floor in the performance curve. We propose a new algorithm that resolves trapping sets and lowers the error floor. The new algorithm, called Syndrome Bit Flipping (SBF), computes the sum of adjacent parity violations at each symbol node. Bits are flipped by comparing the syndrome sum against a time-varying threshold called the decoding key. SBF is compared to other bit-flipping decoders on the Binary Symmetric Channel (BSC), and is demonstrated as a post-processing step for a Noisy Gradient Descent Bit-Flipping (NGDBF) hardware decoder. We demonstrate the post-processing method for an LDPC code defined in the 802.3an standard, and find that the frame error rate is improved by at least two orders of magnitude, even as the required iterations are reduced by 33%.